Solid-Phase Extraction of Catechin Compounds From Green Tea by Catechin Molecular Imprinted Polymers - Tian, M.; Zhang, H.; Row, K.H. (Asian Journal of Chemistry, 2012)
Catechin compounds, (+) catechin (+C), epicatechin (EC), (-) epigallocatechin (EGC) and (-) epigallocatechin gallate (EGCG) were extracted from green tea by hot water and then separated using molecular imprinted polymer (MIP) sorbents in solid-phase extraction (SPE). The MIPs were synthesized using catechin templates, methacrylic acid (MAA) monomer, ethylene glycol dimethacrylate (EGDMA) cross-linker and a,a¢-azobis(isobutyronitrile) (AIBN) initiator. Total catechin adsorption isotherms for catechin-MIPs and non-template imprinted polymer (NIP) were compared, allowing a suitable catechin-MIP (EGCG-MIP) sorbent to be selected for the separation of catechin compounds from green tea extract solution by an optimized SPE procedure and the recovery of (-) epigallocatechin, (+) catechin, epicatechin and (-) epigallocatechin gallate were 73.2, 91.7, 80.5 and 86.9 %, respectively.